Molecular characterization and phylogeny of Shiga toxin–producing Escherichia coli isolates obtained from two Dutch regions using whole genome sequencing. (July 2016) - Ferdous, M.; Friedrich, A.W.; Grundmann, H.; de Boer, R.F.; Croughs, P.D.; Islam, M.A.; Kluytmans-van den Bergh, M.F.Q.; Kooistra-Smid, A.M.D.; Rossen, J.W.A.
Abstract: Shiga toxin–producing Escherichia coli (STEC) is one of the major causes of human gastrointestinal disease and has been implicated in sporadic cases and outbreaks of diarrhoea, haemorrhagic colitis and haemolytic uremic syndrome worldwide. In this study, we determined the molecular characteristics and phylogenetic relationship of STEC isolates, and their genetic diversity was compared to that of other E. coli populations. Whole genome sequencing was performed on 132 clinical STEC isolates obtained from the faeces of 129 Dutch patients with gastrointestinal complaints. STEC isolates of this study belonged to 44 different sequence types (STs), 42 serogenotypes and 14 stx subtype combinations. Antibiotic resistance genes were more frequently present in stx 1-positive isolates compared to stx 2 and stx 1 + stx 2–positive isolates. The iha, mchB, mchC, mchF, subA, ireA, senB, saa and sigA genes were significantly more frequently present in eae -negative than in eae -positive STEC isolates. Presence of virulence genes encoding type III secretion proteins and adhesins was associated with isolates obtained from patients with bloody diarrhoea. Core genome phylogenetic analysis showed that isolates clustered according to their ST or serogenotypes irrespective of stx subtypes. Isolates obtained from patients with bloody diarrhoea were from diverse phylogenetic backgrounds. Some STEC isolates shared common ancestors with non-STEC isolates. Whole genome sequencing is a powerful tool for clinical microbiology, allowing high-resolution molecular typing, population structure analysis and detailed molecular characterization of strains. STEC isolates of a substantial genetic diversity and of distinct phylogenetic groups were observed in this study.